Children with mixed developmental language disorder have more insecure patterns of attachment - Adele Assous (BMC Psychology, 2018)
Abstract Background Developmental Language disorders (DLD) are developmental disorders that can affect both expressive and receptive language. When severe and persistent, they are often associated with psychiatric comorbidities and poor social outcome. The development of language involves early parent-infant interactions. The quality of these interactions is reflected in the quality of the child’s attachment patterns. We hypothesized that children with DLD are at greater risk of insecure attachment, making them more vulnerable to psychiatric comorbidities. Therefore, we investigated the patterns of attachment of children with expressive and mixed expressive- receptive DLD. Methods Forty-six participants, from 4 years 6 months to 7 years 5 months old, 12 with expressive Specific Language Impairment (DLD), and 35 with mixed DLD, were recruited through our learning disorder clinic, and compared to 23 normally developing children aged 3 years and a half. The quality of attachment was measured using the Attachment Stories Completion Task (ASCT) developed by Bretherton. Results Children with developmental mixed language disorders were significantly less secure and more disorganized than normally developing children. Conclusions Investigating the quality of attachment in children with DLD in the early stages could be important to adapt therapeutic strategies and to improve their social and psychiatric outcomes later in life.